Prevalence and Characteristics of Interpersonal Violence in People Dying From Suicide in Victoria, Australia. (January 2018) - MacIsaac, Michael B; Bugeja, Lyndal; Weiland, Tracey; Dwyer, Jeremy; Selvakumar, Kav; Jelinek, George A
Victims of interpersonal violence are known to be at increased risk of suicidal ideation and attempts; however, few data exist on the impact that violence has on the risk of death from suicide. This study examined 2153 suicides (1636 males and 517 females) occurring between 2009 and 2012. Information was sourced from the Coroners Court of Victoria's Suicide Register, a detailed database containing information on all Victorian suicides. Forty-two percent of women who died from suicide had a history of exposure to interpersonal violence, with 23% having been a victim of physical violence, 18% suffering psychological violence, and 16% experiencing sexual abuse. A large number of men who died from suicide had also been exposed to interpersonal violence, many of whom had perpetrated violence within the 6 weeks prior to their death. Targeted prevention, particularly removing barriers for men to seek help early after perpetrating violence is likely to have benefits in preventing suicide in both men and women.